PHILOS Plate Plus Oblique Insertion of Autologous Fibula for 2-Part Proximal Humerus Fractures With Medial Column Disruption: A Retrospective Study. (4th March 2021) - Shu, Ying; Chen, Meiji; Yu, Weiguang; Ge, Zhe; Hu, Hao; Zhang, Xinchao; Zeng, Xianshang; Liu, Xiangzhen
Introduction: The aim of this retrospective study was to evaluate the outcomes of older patients with 2-part proximal humerus fractures (PHFs) with medial column disruption stabilized using a proximal humeral internal locking system (PHILOS) plate plus oblique insertion of autologous fibula as a primary procedure. Materials and Methods: Data involving 112 patients (112 shoulders) sustaining 2-part PHFs with medial column disruption treated with PHILOS plate plus oblique insertion of autologous fibula as a primary procedure during 2012-2019 were identified. The median follow-up was 36 months (range: 11.2-43.5 months). The primary endpoint was the Constant scores and American Shoulder and Elbow Surgeons (ASES) scores. The secondary endpoint was the main orthopedic complication rate. Results: The median Constant and ASES scores were 78 (range, 52-95) and 77 (range, 62-96) at the final follow-up, respectively. The main orthopedic complication rate was 10.7% (12/112). Twelve orthopedic complications in 8 patients were detected, and they involved loss of reduction, varus collapse, aseptic loosening, mal-union, revision, and intolerable shoulder pain. Of these complications, 3 (2.6%) involved loss of reduction, 2 (1.7%) involved varus collapse, 3 (2.6%) involved aseptic loosening, 1 (0.8%) involved mal-union, 2 (1.7%) required revision surgery, and 1 (0.8%) presented intolerable shoulder pain. Conclusion: PHILOS plate plus oblique insertion of autologous fibula as a primary procedure may yield good functional outcomes and a low rate of the main orthopedic complications.